Effective interpretation using various media toward mindfulness: a case study of Malacca - Md Noor, Shuhaida; Rasoolimanesh, Mostafa S.; Ganesan, Vithya; Jaafar, Mastura (Routledge, 2015)
Effective interpretation among visitors to heritage sites contributes towards achieving sustainable tourism. Mindful visitors are more likely to be interested in being educated and learning about a site; therefore, mindfulness can play a key role in the formation of effective interpretations. Diverse media communicates with visitors in different ways and has various effects which can improve mindfulness among heritage site visitors. This study aims to investigate the effects of three different media, namely exhibitions, guided tours (GT) and printed materials (PM) on enhancing mindfulness. A questionnaire was developed and administered to approximately 200 visitors at 6 heritage sites across Malacca City in Malaysia, which was recognised as a UNESCO World Heritage Site in 2008. Partial least-squares structural equation modelling was used to analyse the data. The findings revealed that PM were the most effective medium in improving mindfulness among visitors to the selected heritage sites, followed by exhibitions. The results also indicated that GT did not have any significant effect on improving visitor mindfulness. These findings can assist organisations responsible for the management of heritage sites to improve the mindfulness of visitors by identifying the most efficacious forms of media.